Analysis of Technical Efficiency of Guava Farmers in Yobe State: A Stochastic Frontier Approach - S. A., Okpachu; J. D., Moses (International Journal For Research In Agricultural And Food Science, 2019)
This study was carried out to analyse the technical efficiency of Guava farmers in Yobe State. A multistage sampling technique was employed to select a total of 200 respondents from Potiskum and Fune Local Government Areas for the study. Data collected were analysed using frequency distribution, means and percentages. A Stochastic Frontier Production Function which incorporated inefficiency causes were estimated using Maximum Likelihood Estimation technique. The results of the stochastic frontier function analyses revealed a mean technical efficiencies levels of 74%, implying that there was scope for increasing efficiencies by 26%. The main sources of technical inefficiencies were years of farming experience, extension contact, membership of cooperative societies, amount of credit obtained and educational level. The study recommends that extension contact, years of cooperative membership and access to credit were the sources of the inefficiencies and should be addressed through adequately trained and equipped extension workers, right use of credit facilities and the formation of cooperative societies and making membership a condition for microcredit benefit.